Design and Construction of Academic Information System Website at PKBM As-salaam using the RAD Method - Arjun Haberta; Suhartini; Phinton Panglipur (Yayasan Kita Menulis, 2026)
This research aims to design and develop a web-based information system for Community Learning Activity Center As-Salaam using the Rapid Application Development method. The purpose is based on the fact that the current administrative processes are still carried out manually, either through printed forms or using Microsoft Word, which poses risks of input errors in student data and difficulties in delivering class schedule information to relevant parties. The proposed information system is designed to improve efficiency and accuracy in administrative management, including student registration, class scheduling, and student data processing. The RAD approach is chosen because it enables fast and iterative system development by involving users in every development stage, ensuring that the system is responsive to real user needs. The system will be developed using PHP as the programming language and MySQL as the database. The implementation is expected to facilitate administrative processes, improve data accuracy, accelerate data-driven decision-making, and provide more transparent and efficient services. Ultimately, PKBM As-Salaam is expected to deliver better and more modern non-formal education services.